Penguatan Literasi Matematika dan Sains Melalui Pemberdayaan Karang Taruna Guyub Rukun RT 02 RW 04 Kelurahan Mangunsari Kecamatan Gunungpati Kota Semarang - Isti Hidayah; Wiyanto; Amidi, Amidi; Evany Sofia Prameswari (LPPM UMRI, 2024)
Youth Organization Guyub Rukun, which is only 4 years old, is still minimal in participating in contributing to the implementation of the neighborhood program. This community service activity aims to strengthen the Neighborhood Mangunsari literacy environment, especially with Mathematics and Science literacy which is part of the Community Reading Park management carried out by Youth Organization Guyub Rukun. Through the empowerment of Youth Organization Guyub Rukun, it is hoped that it can strengthen the literacy of residents of RT 02 RW 04 Mangunsari. The program is implemented with the principle of empowerment, as well as a collaborative-participatory approach. The methods of activities that have been carried out are training, ToT (Training of Trainers), simulation, and practice with assistance. The results showed an increase in knowledge, skills, and positive attitudes of the target partners in the management of Community Reading Park and it facilitating Mathematics and Science literacy activities for children in RT 02 RW 04 Mangunsari, Gunungpati Semarang.